Phase 2B study of inhaled RVT-1601 for chronic cough in idiopathic pulmonary fibrosis: a multicenter, randomized, placebo-controlled study (SCENIC Trial) - Martinez, Fernando J.; Wijsenbeek, Marlies S.; Raghu, Ganesh; Flaherty, Kevin R.; Maher, Toby M.; Wuyts, Wim A.; Kreuter, Michael; Kolb, Martin; Chambers, Daniel C.; Fogarty, Charles; Mogulkoc, Nesrin; Tutuncu, Ahmet S.; et al. (American journal of respiratory and critical care medicine, 2022)
Rationale: Chronic cough remains a major and often debilitating symptom for patients with idiopathic pulmonary fibrosis (IPF). In a phase 2A study, inhaled RVT-1601 (cromolyn sodium) reduced daytime cough and 24-hour average cough counts in patients with IPF. - - Objectives: To determine the efficacy, safety, and optimal dose of inhaled RVT-1601 for the treatment of chronic cough in patients with IPF. - - Methods: In this multicenter, randomized, placebo-controlled phase 2B study, patients with IPF and chronic cough for ⩾8 weeks were randomized (1:1:1:1) to receive 10, 40, and 80 mg RVT-1601 three times daily or placebo for 12 weeks. The primary endpoint was change from baseline to end of treatment in log-transformed 24-hour cough count. Key secondary endpoints were change from baseline in cough severity and cough-specific quality of life. Safety was monitored throughout the study. - - Measurements and Main Results: The study was prematurely terminated owing to the impact of the coronavirus disease (COVID-19) pandemic. Overall, 108 patients (mean age 71.0 years, 62.9% males) received RVT-1601 10 mg (n = 29), 40 mg (n = 25), 80 mg (n = 27), or matching placebo (n = 27); 61.1% (n = 66) completed double-blind treatment. No statistically significant difference was observed in the least-square mean change from baseline in log-transformed 24-hour average cough count, cough severity, and cough-specific quality of life score between the RVT-1601 groups and the placebo group. The mean percentage change from baseline in 24-hour average cough count was 27.7% in the placebo group. Treatment was generally well tolerated. - - Conclusions: Treatment with inhaled RVT-1601 (10, 40, and 80 mg three times a day) did not provide benefit over placebo for the treatment of chronic cough in patients with IPF.